Accelerated fuel cell tests of anodic Pt/Ru catalyst via identical location TEM: New aspects of degradation behavior. (5th October 2017) - Hengge, K.; Gänsler, T.; Pizzutilo, E.; Heinzl, C.; Beetz, M.; Mayrhofer, K.J.J.; Scheu, C.
Abstract: In the present work the stability, chemical composition and structure of a Pt/Ru catalyst alloy with a nominal ratio of 1/1 is investigated. The same catalyst particles are analyzed before and after potential cycling experiments using identical location transmission electron microscopy. The experiments were performed at room temperature at [0–1.0] VRHE and [0–1.2] VRHE to simulate conditions occurring during ramping up of fuel cells. With decreasing maximum potential value a higher stability is found. Dissolution and dealloying are identified to be the main degradation mechanisms during potential cycling with Ru being dissolved preferably. Also agglomeration and Ostwald ripening are taking place, the frequency decreasing the longer the experiment is performed. Advanced in-depth analysis of potential-dependent reshaping mechanisms are performed by calculating the three-dimensional volume of single particles both in the as-prepared state and after potential cycling experiments using electron tomography data. Evaluation of the volume-specific change of the accessible surface area of the catalyst helps to understand fuel cell performance deterioration. Highlights: Microstructural TEM analysis of a 1/1 Pt/Ru alloy on HSAC support. CO stripping shows improved CO tolerance of HT-PEMFC anodes using Pt/Ru as catalyst. Degradation analysis via identical location TEM (IL-TEM). Electron tomography reveals degradation behavior of single Pt/Ru particles in 3D.